2014
DOI: 10.1371/journal.pone.0105036
|View full text |Cite|
|
Sign up to set email alerts
|

Movement Coordination during Conversation

Abstract: Behavioral coordination and synchrony contribute to a common biological mechanism that maintains communication, cooperation and bonding within many social species, such as primates and birds. Similarly, human language and social systems may also be attuned to coordination to facilitate communication and the formation of relationships. Gross similarities in movement patterns and convergence in the acoustic properties of speech have already been demonstrated between interacting individuals. In the present studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 62 publications
7
71
0
Order By: Relevance
“…Previous studies indicated that the extent of synchrony represents rapport level between interactants (Bernieri et al 1988;Latif et al 2014). CAT (Giles et al 1991) considers the convergent process of conversational behavior based on the intimacy between interactants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that the extent of synchrony represents rapport level between interactants (Bernieri et al 1988;Latif et al 2014). CAT (Giles et al 1991) considers the convergent process of conversational behavior based on the intimacy between interactants.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Communication Accommodation Theory (CAT) proposes that conversational features, including vocal patterns or gestures, become convergent with increasing intimacy between participants (Giles et al 1991), and several studies have found that relationship profile (e.g., closeness) precedes synchrony, and thus, the extent of synchrony seems to represent the rapport level or relationship quality 1 3 between interactants. Bernieri et al (1988) demonstrated that infants showed more coordinated movement toward adults with whom they were acquainted than with unacquainted adults, and friends have been found to exhibit more synchrony compared to strangers (Latif et al 2014). Similarly, synchronous movement (such as stepping) has been observed to decrease in situations in which the relationship is not well-established (Miles et al 2010).…”
Section: Representing and Bonding: The Extent Of Synchrony And Its Bomentioning
confidence: 98%
“…However, while such rhythmic or temporally stable behaviours do play an important role in IPS, there are many other potential sources of unintentional coordination that need to be taken into account if it comes to naturalistic interactions [30]. Real-world social interactions are seldom perfectly rhythmic but rather highly complex and unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…Speech is not an isolated channel of communication; it cooccurs in rich interactional contexts. Beyond acoustic and articulatory parameters, spoken communication is accompanied by non-verbal modalities such as body posture, eye gaze direction, head movement, and facial expressions, all of which have been shown to contribute to comprehension and may thus be considered relevant parameters to measure(Cummins, 2012;Latif, Barbosa, Vatiokiotis-Bateson, Castelhano, & Munhall, 2014;Prieto, Puglesi, Borràs-Comes, Arroyo, & Blat, 2015;Rochet-Capellan, Laboissière, Galván, & Schwartz, 2008; Yehia, Rubin, & Vatiokiotis-Bateson, 1998).…”
mentioning
confidence: 99%